THE QUALITY IMPROVEMENT OF PRIMER PACKAGING PROCESS USING SIX SIGMA METHODOLOGY - Prima Ditahardiyani; Ratnayani Ratnayani; M. Angwar (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2008)
The implementation of Six Sigma has become a common theme in many organizations. This paper presents the Six Sigma methodology and its implementation in a primer packaging process of Cranberry drink. DMAIC (Define, Measure, Analyze, Improve and Control) approach is used to analyze and to improve the primer packaging process, which have high variability and defects output. After the improvement, the results showed that there was an increasing sigma level. However, it is not significantly and has not achieved the world standard quality, yet. Therefore, the implementation of Six Sigma in primer packaging process of Cranberry drink still has a room for doing a further research.